การเพิ่มประสิทธิภาพของ LSGM อิเล็กโทรไลต์ สำหรับใช้งานในเซลล์เชื้อเพลิงชนิดออกไซด์แข็ง - นวรัตน์ คำศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
The solid electrolyte material La₀.9Sr₀.₁Ga₀.₈Mg₀.₂O₃-δ (LSGM) perovskite oxide is a potential electrolyte for intermediate-temperature solid oxide fuel cells (SOFCs). To reduce polarization resistance in fuel cell, porous LSGM was developed by adding porous LSGM structure onto the surface of dense LSGM. The influencing factors such as electrode coating technique, a variation of porous former and the sintering temperature were investigated. The characterization of porous LSGM material included x-ray powder diffraction (XRD), electrochemical impedance spectroscopy (EIS) and scanning electron microscopy (SEM). The lowest polarization resistance of 3.56 Ω·cm⁻² was achieved from the porous LSGM material made from 40% rice starch and 1450°C sintering temperature in asymmetric cell. The single cell performance test of the optimized porous LSGM was reported as 649.37 mW·cm⁻² which is higher than a maximum power density of cell with a regular LSGM as 319.91 mW·cm⁻² at 800°C.